2022
DOI: 10.52547/ijimes.2.4.20
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital Externalities and Productivity in Cities

Abstract: Human Capital Theory states that individuals invest in their human capital in order to enhance own productivity which is in turn rewarded by higher wages. The theory asserts that investments in human capital are undertaken by individuals until the point where the marginal productivity gained equals the marginal opportunity cost (from the individual's viewpoint). Benefits of human capital accumulation by a person need not pertain to that person solely. An individual's investment in her own human capital may als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…), and the absence of merit-based rewards as damages. These findings align with the research results of previous research (Samadzad & Hashemi, 2022;Tanhaei et al, 2018), which identified a salary and wage system not commensurate with the private sector as one of the most critical damages.…”
Section: Discussionsupporting
confidence: 92%
“…), and the absence of merit-based rewards as damages. These findings align with the research results of previous research (Samadzad & Hashemi, 2022;Tanhaei et al, 2018), which identified a salary and wage system not commensurate with the private sector as one of the most critical damages.…”
Section: Discussionsupporting
confidence: 92%